2008
DOI: 10.3390/molecules14010019
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Non-peptidic Cysteine Protease Inhibitors of P. falciparum Derived from Etacrynic Acid

Abstract: A series of etacrynic acid derivatives was synthesized and screened for their in vitro activity against Plasmodium falciparum, as well as their activity against recombinantly expressed falcipain-2 and -3. The two most active compounds of the series displayed IC50 values of 9.0 and 18.8 μM against Plasmodia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The biotinylated compound (Fig. (13)) is a moderate inhibitor of Falcipain 2 and 3 and also displays modest activity against the W2 strain of P. falciparum [137].…”
Section: Falcipain Inhibitorsmentioning
confidence: 99%
“…The biotinylated compound (Fig. (13)) is a moderate inhibitor of Falcipain 2 and 3 and also displays modest activity against the W2 strain of P. falciparum [137].…”
Section: Falcipain Inhibitorsmentioning
confidence: 99%
“…Compound 24 was identified as the best FPs inhibitor. The investigators recommended future studies to evaluate the affinity binding properties of the identified compound, and to synthesize further peptidomimetic CPIs with etacrynic acid amides [134] .…”
Section: C] Peptidomimetic Inhibitorsmentioning
confidence: 99%
“…The falcipain-3 inhibitors used in the QSAR studies were taken from a recent series of papers [4,10,11]. The geometries of ligands were optimized by the conjugate gradient method of energy minimization with the Tripos force field and Gasteiger-Hückel charges for all atoms until a gradient of 0.01 kcal mol −1 Å −1 was reached.…”
Section: Preparation Of the Ligand For Dockingmentioning
confidence: 99%
“…They have been found to be localized in the food vacuole, and are able to degrade hemoglobin [3]. So far, several peptidic, peptidomimetic, as well as nonpeptidic cysteine protease inhibitors have been synthesized and tested against malaria parasites [4].…”
Section: Introductionmentioning
confidence: 99%